2018
DOI: 10.3390/ijms19061770
|View full text |Cite
|
Sign up to set email alerts
|

Farrerol Relieve Lipopolysaccharide (LPS)-Induced Mastitis by Inhibiting AKT/NF-κB p65, ERK1/2 and P38 Signaling Pathway

Abstract: Farrerol has been proved to have an anti-inflammatory effect. However, the effects of farrerol on mastitis have not been investigated. This study was aimed to investigate the effect and mechanism of farrerol in lipopolysaccharide (LPS)-induced mouse mastitis and LPS-induced inflammatory response of mouse mammary epithelial cells (mMECs). In vivo, LPS were injected to the tetrad pair of nipples for establishing mouse mastitis, and then tested the effect of farrerol on histopathological changes, inflammatory res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…Studies have shown that when AKT phosphorylation is induced and the NF‐κB signalling pathway is subsequently activated, NF‐κB located in the cytoplasm induces phosphorylation of NF‐κBp65. In addition, phosphorylated NF‐κBp‐P65 can be transferred to the nucleus to regulate transcription of pro‐inflammatory mediators 23 . Our results showed that the levels of P65 phosphorylation were observably down‐regulated at the expression of proteins in neonatal MI model rats after treatment with diosmetin.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Studies have shown that when AKT phosphorylation is induced and the NF‐κB signalling pathway is subsequently activated, NF‐κB located in the cytoplasm induces phosphorylation of NF‐κBp65. In addition, phosphorylated NF‐κBp‐P65 can be transferred to the nucleus to regulate transcription of pro‐inflammatory mediators 23 . Our results showed that the levels of P65 phosphorylation were observably down‐regulated at the expression of proteins in neonatal MI model rats after treatment with diosmetin.…”
Section: Discussionmentioning
confidence: 67%
“…The protein kinase B (AKT) signalling pathway work on a survival signal during myocardial ischaemia, and activation of this signal act on the mitochondrion, thereby exerts anti‐apoptotic effects via upstream and downstream signalling 21,22 . Studies have shown that P13K and AKT are involved in the regulation of NF‐κB signalling, AKT could up‐regulate the expression of IκB (NF‐κB inhibition of protein), while NF‐κB signalling plays an important role in regulating the release of cytokines and chemokines 23 . Nrf2, belongs to the CNC family of transcription factors and is a key transcription factor against oxidative stress, controlling various antioxidant genes and enzymes 24 …”
Section: Introductionmentioning
confidence: 99%
“…Farrerol suppressed LPS‐induced IL‐6 and IL‐8 production in human gingival fibroblasts by inhibition of phosphoinositide 3‐kinase/protein kinase B/NF‐κB signaling pathway (Wang, Zhang, & Yu, ). A recent study showed that farrerol relieves LPS‐induced mouse mastitis and inhibits LPS‐induced inflammatory response of mouse mammary epithelial cells by suppressing the protein kinase B/NF‐κB, extracellular regulated protein kinase 1/2 (ERK1/2) and P38 pathways (Li et al, ). Thus, we inferred that farrerol might suppress the NF‐κB activation in MPP + ‐induced BV‐2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The MAPKs perform critical roles in controlling cellular responses to stress and activating NF-κB [32].…”
Section: Discussionmentioning
confidence: 99%